ZnCl2‐Promoted Asymmetric Hydrogenation of β‐Secondary‐Amino Ketones Catalyzed by a P‐Chiral Rh–Bisphosphine Complex1. (29th December 2014) - Hu, Qiupeng; Zhang, Zhenfeng; Liu, Yangang; Imamoto, Tsuneo; Zhang, Wanbin
Abstract A new catalytic system has been developed for the asymmetric hydrogenation of β‐secondary‐amino ketones using a highly efficient P‐chiral bisphosphine–rhodium complex in combination with ZnCl2 as the activator of the catalyst. The chiral γ‐secondary‐amino alcohols were obtained in 90–94 % yields, 90–99 % enantioselectivities, and with high turnover numbers (up to 2000 S/C; S/C=substrate/catalyst ratio). A mechanism for the promoting effect of ZnCl2 on the catalytic system has been proposed on the basis of NMR spectroscopy and HRMS studies. This method was successfully applied to the asymmetric syntheses of three important drugs, (S)‐duloxetine, (R)‐fluoxetine, and (R)‐atomoxetine, in high yields and with excellent enantioselectivities.